Validitas Modul Ekologi Hewan Berdasarkan Hasil Identifikasi Spesies Capung (Odonata) - Wihardi, Andre (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
One of the teaching materials that is often used is modules. A module is a unit of learning material that can be studied by students independently. It contains clear components and instructions, so that students can follow it sequentially without teacher intervention. This research aims to determine the feasibility of the animal ecology module based on the results of identifying dragonfly species (Odonata) found in the Jangkok River, Mataram City. The research instrument used was a validation sheet, which includes aspects of format, content, language, simplicity, illustrations, media quality and attractiveness. This type of research is development research (Research and Development) with a 4D model. Based on the results of the analysis of the feasibility of the Animal Ecology Module from the validation results of 3 expert validators and readability tests of 15 respondents (students who have taken the Animal Ecology course) the results obtained were content/material 82%, language 85% and appearance 92.5%, it was concluded that The Animal Ecology Module is declared appropriate and not revised.